"Ruffled by the number of windows": The 1948 Halberstam House by Henry Kulka - Jacobson, Cherie (Architectural History Aotearoa, 2024)
In March 1940 architect Henry Kulka arrived in New Zealand as a refugee of the Second World War. He had enjoyed a successful career in Vienna, including collaborations with his former teacher Adolf Loos. Kulkaʹs wife Hilda followed with the coupleʹs children a few weeks later and during her journey she met another refugee family, the Halberstams ‐ Hugo, Martha and their daughter Lucie. Eight years later Henry Kulka designed a house for a section the Halberstams had bought in Karori. In an oral history interview with Lucie, she recalled that once the house was completed, her parents invited people they had met while renting in Kelburn to visit their new home. The feedback received about the number of windows and the wood‐panelled living and dining room gave the distinct impression that their former neighbours felt they had built a house "above [their] social level.ʺ This paper looks at the reaction to the Halberstam House and similar houses built by émigré architects when they were completed. It concludes with the perspective of a current inhabitant ‐ how well does it suit contemporary living?.